Estado como agente ativo da economia chinesa: interpretações sobre os 40 anos da política de reforma e abertura - Silveira, Janaína Camara da (Universidade do Vale do Rio dos Sinos, 2018)
China has gone through four decades of transition from an agrarian to an industrial and service economy based on a state-led process ignited with the reform and opening up policy in 1978. China has chosen experimentalism and gradualism as guides for structural reforms, which also meant the creation and adaptation of its institutions, many of them adopted as a transitional solution. In four decades, China became increasingly important in the global scenario, whether through its exports, the foreign investment it receives and provides to other countries, the multilateral financing mechanisms it has launched or its growing urban consumer market. This process is subject of much debate. The present work contributes to this discussion by displaying China's economic historiography since the arrival of the Communist Party to power and by exposing the instruments used by the state on conducting growth and economic development. It also shows the main interpretations and the author’s as well of this phenomenon in terms of role of the State and insertion in the global economy.
Keywords: China; Desenvolvimento; Estado; Mercado; Transição; China; Development; State; Market; Transition; ACCNPQ::Ciências Sociais Aplicadas::Economia